De‐escalation of therapy for pediatric medulloblastoma: Trade‐offs between quality of life and survival. Issue 7 (24th February 2014) - Henrich, Natalie; Marra, Carlo A.; Gastonguay, Louise; Mabbott, Donald; Malkin, David; Fryer, Chris; Bouffet, Eric; Taylor, Michael D.; Hukin, Juliette; Scantlebury, Nadia; Lynd, Larry
<x xml:space="preserve">Abstract</x> Background Treatment intensity for pediatric medulloblastoma may vary depending on the type of medulloblastoma. In some cases, the dose of radiation may be reduced or eliminated. Correspondingly, there may be trade‐offs between quality of life and survival. In this study, focus groups were conducted with parents and clinicians to explore their opinions about these trade‐offs as well as the alignment/misalignment between parents and clinicians regarding the trade‐offs. Methods One hour semi‐structured focus groups were conducted with parents of children with medulloblastoma and health care providers who were involved in the care of these children. Results Parents and providers showed differences in which factors they believe have the greatest impact on quality of life for children with medulloblastoma and their families. For parents, the most important factor is social functioning and their child's ability to make friends and have a social life. In contrast, providers thought that parents cared most about their child's cognitive functioning and ability to attend and perform in school. Conclusion Understanding parents' perspectives on quality of life is important in terms of providing support services that target the areas that the parents prioritize. The types of functioning that are most strongly correlated with quality of life from the parents' perspective may be the ones that should be targeted to protect during treatment. Pediatr Blood Cancer 2014;61:1300–1304. © 2014 Wiley Periodicals, Inc.